The Life of Our Savior Jesus Christ : Three Hundred and Sixty-Five Compositions from the Four Gospels - Tissot, J. James (versión e ilustración) (Sampson Low, Marston and Company)
Obra en dos volúmenes que trata sobre la vida de Jesucristo: infancia, predicación, semana santa, pasión y resurreción.